Building a cluster of NLR genes conferring resistance to pests and pathogens: the story of the Vat gene cluster in cucurbits. (1st April 2021) - Chovelon, Véronique; Feriche-Linares, Rafael; Barreau, Guillaume; Chadoeuf, Joël; Callot, Caroline; Gautier, Véronique; Le Paslier, Marie-Christine; Berad, Aurélie; Faivre-Rampant, Patricia; Lagnel, Jacques; Boissot, Nathalie
Abstract: Most molecularly characterized plant resistance genes (R genes) belong to the nucleotide-binding-site-leucine-rich-repeat (NLR) receptor family and are prone to duplication and transposition with high sequence diversity. In this family, the Vat gene in melon is one of the few R genes known for conferring resistance to insect, i.e., Aphis gossypii, but it has been misassembled and/or mispredicted in the whole genomes of Cucurbits. We examined 14 genomic regions (about 400 kb) derived from long-read assemblies spanning Vat -related genes in Cucumis melo, Cucumis sativus, Citrullus lanatus, Benincasa hispida, Cucurbita argyrosperma, and Momordica charantia . We built the phylogeny of those genes. Investigating the paleohistory of the Vat gene cluster, we revealed a step by step process beginning from a common ancestry in cucurbits older than 50 my. We highlighted Vat exclusively in the Cucumis genera, which diverged about 20 my ago. We then focused on melon, evaluating a minimum duplication rate of Vat in 80 wild and cultivated melon lines using generalist primers; our results suggested that duplication started before melon domestication. The phylogeny of 44 Vat-CDS obtained from 21 melon lines revealed gain and loss of leucine-rich-repeat domains along diversification. Altogether, we revealed the high putative recognition scale offered in melon based on a combination of SNPs, number of leucine-rich-repeat domains within each homolog and number of homologs within each cluster that might jointly confer resistance to a large pest and pathogen spectrum. Based on our findings, we propose possible avenues for breeding programs.